THE INTRODUCTION OF E-GOVERNMENT IN UKRAINE - Писаренко, В. П. (Scientific Progress & Innovations, 2018)
This article deals with the implementation of e-government in Ukraine's integration into the European Union and the issue of his creation of space which is of particular relevance. The paper analyzes legal acts relating to electronic documentation, digital signature, e-governance. Reduced foreign experience in implementing e-government and public access to information networks of power and capabilities of the population in decision-making to local communities. Formed conclusions that the emergence of new information and communication technologies has given reason to talk about the new telecommunications revolution.